Pembuatan Website untuk Lasika Production - Alvin Ferdinandus; Silvia Rostianingsih; Justinus Andjarwirawan (Jurnal Infra, 2016)
Developments in the field of the stage is now increasingly widespread. More and more people are willing to spend big money to get the quality of a spectacular event., the supplier and the expert in this field is still relatively very little. Lasika now present in Surabaya as one of the oldest home industry to explore the aspect of sound system, rigging, LED, and others. Lasika quality has proven capable and became the mainstay of the city of Surabaya when there are events that bring national artists. To that end, Lasika feel the need to balance between performance and branding is also good for the entire society Surabaya, Indonesia even be able to know the quality offered by Lasika.In this thesis begins, the process of website creation of designs using the use case and the flow chart followed by the creation of websites using Hypertext Preprocessor (PHP) as a programming language and MySQL for its database. Features that will be created that is google calendar, instagram, suggestion, and live chat.Results of the implementation and testing of the website is generating features member profiles, view instagram hashtag, google calendar, suggestion, live chat, and be able to see the products offered by Lasika.